UTILIZATION OF BLACK STICKY RICE FOR BIOETHANOL PRODUCTION AS GASOLINE FUEL BLENDS FOR MOTORCYCLES - Abdul Hamid; Misbakhul Fatah; Tegar Hermawan Priambodo; Septian Dwi Wijaya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Despite possessing non-renewable properties, fossil fuel is still widely used as a major energy source. Subsequently, the fossil fuel demand has been increasing while the supply is depleting over time leading to an energy crisis. Fossil fuel also causes associated environmental problems such as emissions as the primary driver of global warming and climate change. Thereby, the development of alternative fuels, such as bioethanol, is beneficial to combat the fossil fuel challenges. Bioethanol is a promising fuel owing to its renewable and environmentally friendly characteristics. In this study, bioethanol was synthesized by a fermentation process over yeast (Saccharomyces Cerevisiae). The feedstock for this process is an abundant resource namely black sticky rice. Bioethanol resulting from this process was mixed with gasoline and applied to a motorcycle machine. The performance of bioethanol was defined by power, torque, and emission. The proportion of the mixture was varied with bioethanol content of 0%, 10 %, 20 %, 30 %, and 40%. The mixture of bioethanol-gasoline produced higher power and torque value compared to gasoline. The E40 mixture had the highest power and torque value with 8.5 hp and 9.2 Nm respectively. However, the combustion of bioethanol-gasoline resulted in more CO2 emission, while the emissions of O2, NO, and NOx were lower. The lowest NOx emissions content was obtained at E30 and E40 blends, about 7 ppm. Meanwhile, the lowest NO emission content was obtained at E30 and E40 blends, about 6 ppm.